Electrically detected magnetic resonance in semiconductor and carbon nanodevices - Lang, V (2012)
Electrically detected magnetic resonance (EDMR) is a sensitive spectroscopic technique, which can be used to readout few to single electron spins in semiconductor and carbon nanodevices for applications in solid state quantum information processing (QIP). Since only electrically active defects contribute to the EDMR signal, this technique can be used further to investigate defects and impurities in photovoltaic devices, in which they limit the sunlight-to-energy conversion efficiency significantly. Here, I employ X-band EDMR for semiconductor defect analysis and identify the most important recombination centres in Czochralski silicon with oxide precipitates, which can be intentionally grown to confine detrimental metallic impurities to inactive regions of the wafer in order to serve as a defect-free substrate for modern silicon photovoltaic devices. Those experiments show that oxide precipitation is accompanied by the formation of silicon dangling bonds. Furthermore, I describe a very promising route towards the fabrication and readout of few to single electron spins in carbon nanotube devices, which can be characterised structurally via transmission electron microscopy in order to relate their electrical and spin properties with their structure. Finally, I employ EDMR to read out electron spin states in donor-doped silicon field-effect transistors as a prerequisite for their application in QIP. I report on a novel cryogenic probe head for EDMR experiments in resonant microwave cavities operating at 0.35 T (9.7 GHz, X-band) and 3.34 T (94 GHz, W-band). This approach overcomes the inherent limitations of conventional X-band EDMR and permits the investigation of paramagnetic states with a higher spectroscopic resolution and signal intensity. Both advantages are demonstrated and discussed. I further report on a novel mechanism giving rise to the EDMR effect in donor-doped silicon field-effect transistors, which is capable of explaining why the EDMR signal intensities of the conduction electrons are enhanced by a factor of ∼100, while the donor resonance signals increase by a factor of ∼20 from X- to W-band only. The spin-relaxation and dephasing times are extracted from a series of pulsed-EDMR measurements and confirm this model. The author gratefully acknowledges funding from Trinity College Oxford, Department of Materials, EPSRC DTA, and Konrad-Adenauer-Stiftung e.V. (Begabtenförderung).